NEGOTIATING MODERN ISLAMIC IDENTITY: The Political and Sociological Dynamics of Niqabis in Indonesia and Egypt - Qibtiyah, Alimatul; Dzuhayatin, Siti Ruhaini; Bouras, Naima; Noorkamilah, Noorkamilah (UIN Sunan Kudus, 2023)
Type the Arab Springs and the rise of Daesh in Syria and Iraq gave the niqabi women a special stand and visibility they never had before. Some niqabis women became visible sharing during the demonstrations calling for justice and social changes, others who believe in the Salafi jihadi trend were intensely mediatised due to their implication, next to Daesh, in tortures and bomb attacks. The civil societies in Egypt and Indonesia started to shape new calls to ban niqâb and presented it as a danger for the country. In both countries’ controversy has raised among Islamic mass organizations and universities. The Salafi doctrine which control women to cover the body including the face have increased in Egypt by the 70’ and in Indonesia during the 90’. It has entailed deep socio-religious norms’ transformations in both countries, with different impacts. This research focuses on how niqabis negotiate their modern identities in Indonesia and Egypt. It employs mixed method and uses surveys, in-depth interview (life stories), and focus group discussion. This paper would like to expose some results of those investigations happened in Indonesia and Egypt from June to November 2018.